Gender differences in meat-eating behavior and environmental attitudes: the mediating role of the Dark Triad - Mertens, Alica; Krause, Mischa von; Denk, Alexandra; Heitz, Theresia (Universität, 2020)
Recently, Machiavellianism was identified as potential mediator explaining gender differences in meat-eating justification strategies, which in tur...
Deposit date: 2020-07-16
Gesehen am 14.09.2020
Keywords: Forschungsdaten; Datenbank